Software fault location technology under terminal embedded component. Issue 2 (April 2021) - Xu, Min; Lu, XingHua
Abstract: In order to improve the software fault location capability of embedded components of heterogeneous Web server terminals, a software fault location method of embedded components of heterogeneous Web server terminals based on source code fault feature detection is proposed. The original information collection model for software fault detection of embedded components of heterogeneous Web server terminals is constructed, the big data feature quantity of software safety information of embedded components is mined. The spectrum information of software safety information is extracted by adopting a dynamic information fusion method, so as to obtain the fuzzy closeness of software faults. The big data information parameters of embedded component software faults of heterogeneous Web server terminals are adaptively adjusted, and the cross information distribution set of embedded component software faults of heterogeneous Web server terminals is determined. The disturbance of embedded component software faults of heterogeneous Web server terminals is obtained by using the method of limit mining, and the adaptive mining of software faults is realized. Simulation results show that this method is accurate in locating software faults under terminal embedded components, and the software has strong anti-attack ability.